Peningkatan Minat dan Hasil Belajar Biologi Materi Sistem Transportasi Manusia melalui Pembelajaran Role Playing Siswa Kelas VIII-H SMPN 5 Surakarta Semester I Tahun 2013/2014 - RAHMAWATI, BANATI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
SMPN5 Surakarta has outstanding vision and cultured on faith and Piety.the subjects of biology in this Surakarta SMPN5 not as expected, on his way to the front of learning in general should be improved particularly in the teaching of science including biology science subjects. research that has been conducted on 32 students are 47.5% of students who pay attention to the lessons, 12.5% of students dreamy, sleepy students 7.5%, 12.5% of students do not focus on the subject and only 20% of students participate in learning. lack of student interest in the learning process led to the success of student learning achieved suboptimal anyway. Research conducted in the semester began in July to December 2013, with the implementation of measures in October to November 2013 in SMPN5 Surakarta with the subject viii h grade students who are 32 students. On the first cycle students learn in a large group of 8 students in one group, while in the second cycle students learn in small groups, namely 4 students in one group. Each stage of each cycle consisting of planning actions, implementation of action, observation and reflection action. data using quantitative descriptive analysis by comparing the initial conditions of mastery learning cycle 1 and cycle 2. The results showed a significant increase in interest in learning from the initial condition is active only 8 students to 30 students are active, attentive and happy while learning. learning outcomes of students has increased from baseline to 1 cycle of 21%. cycle 1 to cycle 2 increased 6%. learning outcomes from baseline to 2 cycles increased 29% The results of these studies indicate that through role playing learning model can improve student interest and learning outcomes.